Comparative efficacy and safety of first-line antiretroviral therapy for the treatment of HIV infection: a systematic review and network meta-analysis. Issue 11 (November 2016) - Kanters, Steve; Vitoria, Marco; Doherty, Meg; Socias, Maria Eugenia; Ford, Nathan; Forrest, Jamie I; Popoff, Evan; Bansback, Nick; Nsanzimana, Sabin; Thorlund, Kristian; Mills, Edward J
Summary: Background: New antiretroviral therapy (ART) regimens for HIV could improve clinical outcomes for patients. To inform global guidelines, we aimed to assess the comparative effectiveness of recommended ART regimens for HIV in ART-naive patients. Methods: For this systematic review and network meta-analysis, we searched for randomised clinical trials published up to July 5, 2015, comparing recommended antiretroviral regimens in treatment-naive adults and adolescents (aged 12 years or older) with HIV. We extracted data on trial and patient characteristics, and the following primary outcomes: viral suppression, mortality, AIDS defining illnesses, discontinuations, discontinuations due to adverse events, and serious adverse events. We synthesised data using network meta-analyses in a Bayesian framework and included older treatments, such as indinavir, to serve as connecting nodes. We defined network nodes in terms of specific antivirals rather than specific ART regimens. We categorised backbone regimens and adjusted for them through group-specific meta-regression. We used the GRADE framework to interpret the strength of inference. Findings: We identified 5865 citations through database searches and other sources, of which, 126 articles related to 71 unique trials were included in the network analysis, including 34 032 patients randomly assigned to 161 treatment groups. For viral suppression at 48 weeks, compared with efavirenz, the odds ratio (OR) for viral suppression was 1·87 (95% credible interval [CrI] 1·34–2·64) with dolutegravir and 1·40 (1·02–1·96) with raltegravir; with respect to viral suppression, low-dose efavirenz was similar to all other treatments. Both low-dose efavirenz and integrase strand transfer inhibitors tended to be protective of discontinuations due to adverse events relative to normal-dose efavirenz. The most protective effect relative to efavirenz in network meta-analyses was that of dolutegravir (OR 0·26, 95% CrI 0·14–0·47), followed by low-dose efavirenz (0·39, 0·16–0·92). Owing to insufficient data, we could make no conclusions about serious adverse events. Low event rates also limited the quality of evidence with regard to mortality and AIDS defining illnesses. Interpretation: The efficacy and safety of ART has substantially improved with the introduction of newer drug classes of antiretrovirals that are now available to patients and HIV care providers. Their improved tolerance could be part of a larger solution to improve retention, which is a challenge, particularly in low-income and middle-income country settings. Funding: The World Health Organization.